The theosophical enlightenment - Godwin, Joscelyn (Albany : State University of New York Press, 1994)
An enticing intellectual history of various esoteric currents from the early Romantic period to the early twentieth century. The author maintains that the Theosophical Society held a crucial position as the place where all those currents temporarily united, before diverging again.
1. The Worship of the Generative Powers -- 2. The Cult of the Sun -- 3. The Blasphemers -- 4. The Shoemaker and the Squire -- 5. Magicians and Revolutionaries -- 6. Neophytes and Initiates -- 7. Artists and Astrologers -- 8. Animal Magnetism -- 9. Visions in the Crystal -- 10. Hydesville and After -- 11. From the Orphic Circle to the Golden Dawn -- 12. The Way to Christ -- 13. Rosicrucian Pretenders -- 14. Enter Madame Blavatsky -- 15. Wisdom from the East -- 16. The Hermetic Reaction -- 17. The Parting of East and West -- Appendix A: Letter from Rammohun Roy to Robert Dale Owen -- Appendix B: Letter from Hargrave Jennings to Bulwer-Lytton.
Includes bibliographical references (pages 419-434) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Theosophy -- Great Britain -- History; Occultism -- Great Britain -- History; Occultisme -- Grande-Bretagne -- Histoire; Théosophie -- Grande-Bretagne -- Histoire; RELIGION -- Eckankar; BODY, MIND & SPIRIT -- New Thought; Occultism; Theosophy; Great Britain; Geschichte; Okkultismus; Theosophie; Großbritannien; Theosofie; Occultisme; Theosophy -- Great Britain -- History; Occultism -- Great Britain -- History; Geschichte -- 1800-1930; Occultism -- Great Britain -- History; Theosophy -- Great Britain -- History; History